Speleomorphological characteristics of the carst and protection of the underground carst forms in the Skopje Basin - Kolčakovski, Dragan (Macedonian Journal of Ecology and Environment, 1996)
Skopje’s Basin (1840 km2) is located in the center of the Balkan Peninsula , namely in the northern part of Macedonia. The carst in this basin includes 305 km2 or 16, 6 % of its territory. Until these days in the frames of the basin’s area 44 underground carst forms are explored in the scientific literature (1925-1991) namely caves and abysses. It isn’t their definite number because there are possibilities for new investigations. As a result of the researches made until these days basic speleomorphological characteristics of the carst relief in the Skopje’s Basin are showed. We give a special accent on the current problems for the protection of the underground carst forms.